2009
DOI: 10.1097/ccm.0b013e3181a592b3
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with stress cortisol enhances the human systemic inflammatory response to bacterial endotoxin

Abstract: Objective-There is continuing controversy regarding the effect of glucocorticoids on a systemic inflammatory process. Based on a model of glucocorticoid action that includes both pro-and antiinflammatory effects, we used the human experimental endotoxemia model to test the hypothesis that a transient elevation of plasma cortisol to stress-associated levels would enhance a subsequent (delayed) systemic inflammatory response to bacterial endotoxin. Design-Prospective, randomized, double-blind, placebo-controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 55 publications
2
42
0
1
Order By: Relevance
“…For glucocorticoid hormones, it has been demonstrated that they directly can influence immune functioning [Yeager et al, 2009]. Regulation of immune response by HPA‐axis activation is mediated through glucocorticoid signaling, either by increased release of corticosterone from the adrenal gland or increased sensitivity of immune cells by high expression of glucocorticoid receptors (GR) [Tait et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…For glucocorticoid hormones, it has been demonstrated that they directly can influence immune functioning [Yeager et al, 2009]. Regulation of immune response by HPA‐axis activation is mediated through glucocorticoid signaling, either by increased release of corticosterone from the adrenal gland or increased sensitivity of immune cells by high expression of glucocorticoid receptors (GR) [Tait et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…All subjects experienced a transient systemic inflammatory response as previously described (Suffredini et al 1999) that included sequential increases in plasma concentrations of pro-inflammatory IL-6 and anti-inflammatory IL-10. In the Stress Cortisol group, the pro-inflammatory IL-6 response was significantly increased compared to both the Control and Pharmacologic Cortisol groups while the anti-inflammatory IL-10 response was decreased (Yeager et al 2009). We compared the salivary free cortisol concentration that was achieved in vivo during the 6-hour intravenous infusion (Day1) with both the peak IL-6 concentrations (3 hours after LPS injection) and with the total area under curve (AUC) for IL-6 over 8 hours after LPS injection (Day 2).…”
Section: Cortisol Exerts Bi-directional Regulation Of Monocyte Mrna Fmentioning
confidence: 99%
“…It has been recently reported that healthy adults infused with a low dose of cortisol for 6 h exhibited an enhanced IL-6 response to stress compared to the group infused with the higher dose (Yeager et al 2009). The elevated levels of evening cortisol in the children in our study may be sufficient to prime the immune system to elicit a protective effect on URI.…”
Section: Discussionmentioning
confidence: 97%